2007
DOI: 10.1093/icesjms/fsm117
|View full text |Cite
|
Sign up to set email alerts
|

Current status and temporal trends in stocks of European eel in England and Wales

Abstract: Bark, A., Williams, B., and Knights, B. 2007. Current status and temporal trends in stocks of European eel in England and Wales. – ICES Journal of Marine Science, 64: –. An extensive 4-year programme of catchment surveys, data collection, and model development for eels was undertaken to establish the status of the stocks in England and Wales, so that appropriate management action can be taken. Nine test catchments representing different geographical areas and catchment types were studied, covering 14 rivers, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 14 publications
3
49
2
Order By: Relevance
“…The dramatic decline of yellow eels within the Bristol Channel contrasts with the findings of Bark et al (2007) for the tributaries of the upper Severn Estuary, in which sampling was carried out during 1998, 1999 and from 2002 to 2004. This study concluded that the estuary's upper tributaries were at, or approaching their carrying capacity and stressed the importance of later life stage recruitment from estuaries in maintaining freshwater stocks. It would appear from the data presented in Figure 7 that if the River Severn relies on recruitment of yellow eels from its estuary and the Bristol Channel, then a future decline in the associated riverine stock may be expected.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The dramatic decline of yellow eels within the Bristol Channel contrasts with the findings of Bark et al (2007) for the tributaries of the upper Severn Estuary, in which sampling was carried out during 1998, 1999 and from 2002 to 2004. This study concluded that the estuary's upper tributaries were at, or approaching their carrying capacity and stressed the importance of later life stage recruitment from estuaries in maintaining freshwater stocks. It would appear from the data presented in Figure 7 that if the River Severn relies on recruitment of yellow eels from its estuary and the Bristol Channel, then a future decline in the associated riverine stock may be expected.…”
Section: Discussioncontrasting
confidence: 67%
“…Despite the marked decline in the recruitment of glass eels and the general view that yellow eel stocks are declining throughout Europe, Bark et al (2007) have shown that yellow eel populations have remained stable in some UK river systems. They concluded that, despite declining levels of recruitment, many west coast rivers were still at, or near their carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is difficult to understand, at inland sites, the effects of the long-term reduction in glass eel recruitment on the upstream movement process of the yellow eel stage. The initiation and cessation of annual upstream movements of eels in riverine systems is controlled by environmental variables such as water temperature and river discharge (Naismith and Knights 1988; Bark et al 2007;Nzau Matondo et al 2014). As a consequence, fish pass monitoring may play an important role by providing useful information on the upstream migration behavior of the riverine yellow eel (Welsh et al 2015) in the context described above.…”
Section: Introductionmentioning
confidence: 99%
“…The Scenario-based Model for Eel Populations (SMEP) (Aprahamian et al, 2007) and GlobAng (Lambert and Rochard, 2007) share common approaches to modelling eel production within river basins. While there is a lot of growth data eels from UK rivers (Aprahamian, 1988(Aprahamian, , 2000Bark et al, 2007), there is a limited understanding of other processes, or how they might be influenced by density and habitat. Furthermore, the application of spatial models such as these requires the quantification of the eel-producing habitat, and ideally an understanding of the potential production of the various habitats, including how this potential varies with distance from the sea, etc.…”
Section: > Future Developments In Assessment Proceduresmentioning
confidence: 99%